2017
DOI: 10.1111/oli.12148
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Indirect Translation

Abstract: Although indirect translation (ITr) has always been commonly accepted and necessary, it is seldom discussed in translation studies. Issues such as the reasons for ITr, the visibility of ITr, the ways of mediating, the agents and other influential factors in ITr, and the its reception have suggested its complex nature, and thus determined that many facets of ITr remain to be studied. The present article will try to encompass the complexity of ITr by looking into the reasons for translating indirectly, the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Looking at the choices of Quranic verses (above) and their placement and the dedication to the fellow translator (below), one can notice how the translator heavily self-promoted himself within features that also served his attempts at domesticating the content to a more middle-eastern/Arab socio-cultural context. Li (2017) stated that there is a need to consider the power relations between cultures/languages since it is assumed that the indirect translation takes place when both the source language and the target language are not dominant while the mediating language is dominant. This adds weight to the argument of how indirect translation might place the translator in a position where he would make different decisions about his/her translation choices.…”
Section: Analysis Of Prefacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the choices of Quranic verses (above) and their placement and the dedication to the fellow translator (below), one can notice how the translator heavily self-promoted himself within features that also served his attempts at domesticating the content to a more middle-eastern/Arab socio-cultural context. Li (2017) stated that there is a need to consider the power relations between cultures/languages since it is assumed that the indirect translation takes place when both the source language and the target language are not dominant while the mediating language is dominant. This adds weight to the argument of how indirect translation might place the translator in a position where he would make different decisions about his/her translation choices.…”
Section: Analysis Of Prefacesmentioning
confidence: 99%
“…Iraq, a country that chances of its people reading Japanese Literature is limited to say the least, would definitely benefit from a translation of Japanese literature albeit it being an indirect one using an English mediating text. Li (2017) discussed elaborated on this idea in a study titled The Complexity of Indirect Translation Nonetheless, despite its reputation as a reluctant choice and inferior because of its second-hand nature, it has been crucial to the dissemination of literature of non-major cultures or in less spoken languages. World literature would have lost much but for the diverse literary genres and C. Spanish ST Love in the Time of Cholera (1985) by Gabriel García Márquez This pair of preface versus no preface is quite interesting; having read a number of books translated by the Arabic translator, it can be safely said that he rarely provides prefaces.…”
Section: English Preface (Tt2)mentioning
confidence: 99%
“…Indirect translation, also known as 'second-hand translation' (Toury, 1995), 'relay translation' (Dollerup, 2000), 'mediated translation' (Pym, 2011) or 'intermediary translation' (Stroilova & Dmitriev, 2016), means that a text is not translated directly from the source language (SL) into the target language (TL), but instead from SL into an intermediary language, and then from this intermediary language into TL. As Pokorn (2013), Li (2017) and Pięta (2019) point out, indirect translation has always been a common practice but has received surprisingly little attention in theoretical literature. When it is discussed in translation studies, particularly in relation to literary translation, it is typically seen as detrimental to the quality of the text, and especially so in terms of conveying cultural elements (e.g.…”
Section: Literature Overviewmentioning
confidence: 99%
“…A comparative study of multiple translations can also be found inLee (2016).12 This is roughly in line with the parameters of the current Global Chaucers project, which focuses on works published after 1945.13 In the Korean context, a major source of disreputability is the stigmatized but still-frequent practice of indirect (or "relay") translation, particularly through Japanese or English. For more on this phenomenon, including its productive potential for literary study, seeWashbourne (2013),Li (2017), andSamoyault (2020). For a recuperative analysis focused particularly on indirect translations into Korean, seeCho (2011) andLee (2008).14 For names in academic citations of Korean scholarship, I have followed the Western convention of using the surname as a "last name," for ease of reference.…”
mentioning
confidence: 99%
“… In the Korean context, a major source of disreputability is the stigmatized but still‐frequent practice of indirect (or “relay”) translation, particularly through Japanese or English. For more on this phenomenon, including its productive potential for literary study, see Washbourne (2013), Li (2017), and Samoyault (2020). For a recuperative analysis focused particularly on indirect translations into Korean, see Cho (2011) and Lee (2008).…”
mentioning
confidence: 99%